2022
DOI: 10.1038/s41598-022-19897-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of Staphylococcus equorum KM1031 from the high-salt fermented seafood jeotgal under chloramphenicol, erythromycin and lincomycin stresses

Abstract: Staphylococcus equorum strain KM1031 is resistant to chloramphenicol, erythromycin and lincomycin. To shed light on the genetic factors underlying these antibiotic resistances, we determined the global gene expression profile of S. equorum KM1031 using RNA sequencing. During chloramphenicol, erythromycin and lincomycin treatment, 8.3% (183/2,336), 16.0% (354/2,336), and 2.9% (63/2,336) of S. equorum KM1031 genes exhibited significant differences in expression, respectively. These three antibiotics upregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Chloramphenicol down-regulated flagellar gene expression and swimming and swarming motility of Salmonella enterica serovar Typhimurium, but up-regulated genes involved in invasion, attachment, and intracellular survival ( Brunelle et al, 2014 , 2017 ). Transcriptome analysis revealed that chloramphenicol affects global gene expression in multiple bacterial species including such as Streptococcus pneumoniae ( Ng et al, 2003 ), Staphylococcus equorum ( Heo et al, 2022 ), Bacillus subtilis ( Lin et al, 2005 ), Yersinia pestis ( Qiu et al, 2006 ), Thermotoga maritima ( Montero et al, 2007 ), Pseudomonas putida ( Fernandez et al, 2012 ), Myxococcus xanthus ( Yang et al, 2019 ), Enterococcus faecalis ( Tatta et al, 2023 ), and Escherichia coli ( Bie et al, 2023 ). The genes that showed altered expression in response to chloramphenicol are involved in multiple cellular pathways including metabolism, stress response, regulation, and protein biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chloramphenicol down-regulated flagellar gene expression and swimming and swarming motility of Salmonella enterica serovar Typhimurium, but up-regulated genes involved in invasion, attachment, and intracellular survival ( Brunelle et al, 2014 , 2017 ). Transcriptome analysis revealed that chloramphenicol affects global gene expression in multiple bacterial species including such as Streptococcus pneumoniae ( Ng et al, 2003 ), Staphylococcus equorum ( Heo et al, 2022 ), Bacillus subtilis ( Lin et al, 2005 ), Yersinia pestis ( Qiu et al, 2006 ), Thermotoga maritima ( Montero et al, 2007 ), Pseudomonas putida ( Fernandez et al, 2012 ), Myxococcus xanthus ( Yang et al, 2019 ), Enterococcus faecalis ( Tatta et al, 2023 ), and Escherichia coli ( Bie et al, 2023 ). The genes that showed altered expression in response to chloramphenicol are involved in multiple cellular pathways including metabolism, stress response, regulation, and protein biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Chloramphenicol down-regulated flagellar gene expression and swimming and swarming motility of Salmonella enterica serovar Typhimurium, but up-regulated genes involved in invasion, attachment, and intracellular survival (Brunelle et al, 2014(Brunelle et al, , 2017. Transcriptome analysis revealed that chloramphenicol affects global gene expression in multiple bacterial species including such as Streptococcus pneumoniae (Ng et al, 2003), Staphylococcus equorum (Heo et al, 2022), Bacillus subtilis (Lin et al, 2005), Yersinia pestis (Qiu et al, 2006), Thermotoga maritima (Montero et al, 2007), Pseudomonas putida (Fernandez The OP-TR colony variation of V. parahaemolyticus. A small amount of V. parahaemolyticus cells was streaked onto a HI plate containing 0, 0.2 or 0.4 μg/mL chloramphenicol, and then statically incubated at 37°C for 24 h. Pictures were representative of two independent experiments with three replicates each.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reports suggest that this species might influence the sensorial profile of sausages and cheeses through the production of butan‐3‐diol, acetoin and diacetyl (Irlinger et al., 2012; Lee et al., 2018; Stavropoulou et al., 2018), generating pleasant or off‐flavours depending on the ratio between these molecules and other volatile organic compounds (VOCs). However, it was also proved that S. equorum strains isolated from FFs may become resistant to multiple antibiotics through acquisition of mobile genetic elements (Heo et al., 2022).…”
Section: Fermented Foods From the World A Taxonomic Characterisationmentioning
confidence: 99%